Teaching feminism - Perger, Nina (Šolsko polje, 2020)
The aim of this article is to gain insights into how feminist principles, content and practices persist in higher education in times of neoliberal ideology, post-feminism and the intensification of extreme-right wing politics. The main issue the article seeks to address is the state of gender-related and feminist topics in higher education. Their state should be addressed at the intersections of: 1) social context; 2) institutional settings (formalised and officialised gender-related curricula); and 3) intra-institutional practices, such as backlashes to and sanctions against feminist practices. In order to achieve this, we start by briefly sketching the beginnings of women's studies worldwide, and the ambivalences of institutionalising feminist knowledge. We proceed by focusing our discussion on the contemporary social situation, significantly marked by right-wing politics and neoliberal ideology, aiming to constitute feminism as irrelevant on the grounds of an individualised "brave new world", where everything seems possible, achievable and accessible. We continue by focusing our attention on the state of feminist topics in the context of Slovenian higher education. This part is based on document analysis of curricula of various universities in Slovenia (a description of their study courses and programmes: the research shows that gender-related topics are still marginalised within higher education as feminist topics remain rare and optional rather than obligatory. After discussing the barriers and obstacles facing feminism, we conclude with a discussion on feminist persistence and resistance in higher education: it is still persisting despite the backlashes that seek to extort a price for doing feminism, even if feminist practices are forced to take a more subtle form.
Keywords: Feminism; Feminizem; Higher education; odpor; učni programi; Visoko šolstvo; Women's studies; Ženske študije